A Two-Level Finite Element Galerkin Method for the Nonstationary Navier-Stokes Equations II: Time Discretization (Journal of Computational Mathematics, 2004)
In this article we consider the fully discrete two-level finite element Galerkin method for the two-dimensional nonstationary incompressible Navier-Stokes equations. This method consists in dealing with the fully discrete nonlinear Navier-Stokes problem on a coarse mesh with width $H$ and the fully discrete linear generalized Stokes problem on a fine mesh with width $h
Keywords: Navier-Stokes equations; Galerkin method; Finite element.